Awareness and Perception of Computer Ethics by Undergraduates of a Nigerian University - Oyewole, Olawale (Journal of Information Science Theory and Practice, 2017)
The invention of computers is one of the best things that have ever happened to mankind and undergraduate students can benefit immensely from the use of computers. However, observations have showed that in the present Nigerian society, there are a number of issues arising from unethical use of computers. Interactions with some undergraduate students revealed that a majority have fallen into the trap of unethical use of computers at one time or another. This seemingly alarming rate of unethical use of computers therefore calls for concern. A literature search has shown that awareness and perception of computer ethics have not been adequately researched within the Nigerian context. Thus, the main objective of this study was to examine the awareness and perception of computer ethics by undergraduate students in a Nigerian university. Descriptive survey research method was used and the study population was comprised of 12,894 undergraduate students of the University of Ibadan, Nigeria. The multistage random sampling technique was used to select a sample size of 292 and the questionnaire was used to collect data. Findings showed that the level of awareness of respondents on issues associated with computer ethics was high (mean=45.19). A majority of the respondents had a favorable perception of computer ethics and the most prominent factor identified that could hinder adherence to computer ethics as noted by most of the respondents was the poor economic situation of the country. Part of the recommendations was that government at all levels should provide responsible and responsive leadership.